Gamifying the Classroom: The Effect of Quizizz on Vocabulary Retention Among Indonesian Junior High School Students - Husnaini; Surya Amalia; St. Hartina (FOSTER: Journal of English Language Teaching, 2024)
Vocabulary is a key element of English language learning upon which it builds learners´ ability to communicate successfully and improve their overall levels of proficiency in the language. Gamification-based learning platforms have recently garnered a lot of attention in the context of English as a Foreign Language (EFL), as they may potentially enhance student engagement and ultimately lead to better learning outcomes. Even though Quizizz is more widely used in language classrooms, there have been very few pieces of empirical evidence in the literature that state its effectiveness for improving vocabulary mastery among Indonesian junior high school students (in studies using an experimental design). The research sought to determine if Quizizz based gamification significantly enhances students' vocabulary mastery over conventional instructional approaches. In total, a quantitative quasi-experimental design with 62 ninth-grade students at the public junior high school in Indonesia (experimental group n = 32; control group n = 30) was conducted. Data were collected and analyzed using pre-test and post-test a 50-item vocabulary test, descriptive statistics, paired-sample t-tests, and effect size calculation. Results indicated a large gain for the experimental group (mean scores improved from 59.94 to 84.07) compared with the control group, whose means increased from 60.33 to 67.07 Statistical analysis showed significant difference between the pre-test and post-test scores (p <. 001), which indicate that Quizizz is a good tool to improve the students' master of vocabulary. These findings elucidate the pedagogical potentials of gamified learning environments in vocabulary instruction and advocate the infusion of digital gamification instruments with a view to enhancing EFL learning experience for greater motivation, engagement and effectiveness.